Health Promotion Program among Prehypertensive People, Chumphon Sub-District, Moeiwadee District, Roi Et Province - Chatlada Deeprom (Warasan Witthayasat Lae Theknoloyi Mahawitthayalai Mahasarakham, 2019)
This quasi-experimental research aimed to test the effectiveness of the Health Promotion Program among prehypertensive people in Chumphon Sub-District, Moeiwadee District, Roi Et Province. The 68 high risk of high blood pressure participants were divided into 2 groups, an experimental group and a control group. There were 34 people per group. The experimental group was intervened with Health Promotion Program for 10 weeks. The Motivation theory of self-efficacy, the behaviours prevention of 3E and 2S (Eating, Emotion, Exercise, Stop Smoking, Stop Drinking) and the exercise by the 9 tables were applied with the receiving of health promotion program. Previous research have never had exercised by 9 tables in among pre-hypertensive subjects. The data were collected by using a quantitative questionnaire and blood pressure measurement and were analysed for percentage, mean, standard deviation, Paired Samples t-test, and Independent Samples t-test. The results showed that after the intervention of Health Promotion Program the mean score of knowledge about hypertension, perceived severity, self-efficacy, hypertension behaviours prevention of 3E and 2S was higher than in the pre intervention program and higher than the comparison group by a statistically significant difference at p < 0.001. The systolic and diastolic blood pressure were decreased compared with the pre intervention program by a statistically significant difference at p < 0.001. The study suggests that the application of self-efficacy theory together with exercise with “Table 9 Tables” can promote the blood pressure control effectively. We can use the Health Promotion Program among people at risk of hypertension in the community in order to prevent hypertension, which can consequently leads to decreases in a number of hypertension patients.